Limitations in Business Judgement Rule: PT Pertamina, The United States and Australia Comparison - Fitriana, Novia (Universitas Islam Negeri Walisongo Semarang, 2025)
This study aims to examine the application of the Business Judgment Rule (BJR) in the case of PT Pertamina and compare its practice in Indonesia, the United States, and Australia. BJR is a legal doctrine that protects the direction from personal liability for company losses; all business decisions are taken in good faith, with prudence, without conflict of interest, and in the interests of the company. The case of PT Pertamina, related to the investment in the Australian BMG Block, is the focus of the study. The Supreme Court acquitted PT Pertamina (Karen Agustiawan) because the loss was considered a normal business risk, not a state financial loss. Using a normative juridical approach through literature study, the study analyzes the limitations of the application of BJR in third countries. In the United States, BJR applies strict standards through the duty of care and duty of loyalty based on the Model Business Corporations Act. Australia regulates BJR comprehensively in the Corporations Act 2001 with four absolute conditions, including protection in force majeure conditions and a safe harbor mechanism. This comparison emphasizes the importance of clear boundaries to balance legal protection and accountability, especially in the context of state-owned enterprises that are vulnerable to being permitted. The study concluded that BJR is not absolute immunity but rather conditional protection that must be expressly regulated within the legal framework and corporate governance to encourage sound and responsible business decisions. Penelitian ini bertujuan mengkaji penerapan Business Judgment Rule (BJR) dalam kasus PT Pertamina dan membandingkan praktiknya di Indonesia, Amerika Serikat, dan Australia. BJR merupakan doktrin hukum yang melindungi direksi dari pertanggungjawaban pribadi atas kerugian perusahaan, sepanjang keputusan bisnis diambil dengan itikad baik, kehati-hatian, tanpa benturan kepentingan, dan demi kepentingan perseroan. Kasus PT Pertamina terkait investasi Blok BMG Australia menjadi fokus kajian. Mahkamah Agung membebaskan PT Pertamina (Karen Agustiawan) karena kerugian dianggap sebagai risiko bisnis wajar, bukan kerugian riil keuangan negara. Dengan pendekatan yuridis normatif melalui studi kepustakaan, penelitian menganalisis batasan penerapan BJR di ketiga negara. Di Amerika Serikat, BJR menerapkan standar ketat melalui duty of care dan duty of loyalty berdasarkan Model Business Corporate Act. Australia mengatur BJR secara komprehensif dalam Corporations Act 2001 dengan empat syarat mutlak, mencakup perlindungan dalam kondisi force majeure dan mekanisme safe harbour. mengatur BJR secara komprehensif dalam Corporations Act 2001 dengan empat syarat mutlak, mencakup perlindungan dalam kondisi force majeure dan mekanisme safe harbour, melainkan perlindungan bersyarat yang harus diatur secara tegas dalam kerangka hukum dan tata kelola perusahaan guna mendorong keputusan bisnis yang tepat dan bertanggung jawab. Keywords: Business Judgment Rule; Directors; PT Pertamina.